2021
DOI: 10.3897/folmed.63.e52165
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Evaluation of Soft Tissue Chin Thickness in Adult Patients with Skeletal Class II Malocclusion with Various Vertical Growth Patterns: a Cephalometric Study

Abstract: Introduction: Facial soft tissue thickness is important not only for plastic surgeons but also for orthodontists to plan the treatment procedure. Genioplasty, an orthognathic surgery in combination with orthodontic treatment is indicated to restore adequate shape and projection of the chin in the face. It has been performed to enhance soft tissue contours related to disproportion between soft and hard tissue. These treatments require the critical information regarding the relation between soft and hard tissues… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…The influence of the vertical skeletal pattern on facial soft tissue thickness has been reported previously in other populations [31][32][33]. In agreement with our results, a study showed that the hypodivergent group had thicker soft tissue in Me h -Me s and Gn h -Gn s [34]. Previous studies found that hyperdivergent subjects had reduced soft tissue thickness in Rhi h -Rhi s , Ss h -Sn s , and U1-LS, compared to hypodivergent subjects [32,33].…”
Section: Discussionsupporting
confidence: 93%
“…The influence of the vertical skeletal pattern on facial soft tissue thickness has been reported previously in other populations [31][32][33]. In agreement with our results, a study showed that the hypodivergent group had thicker soft tissue in Me h -Me s and Gn h -Gn s [34]. Previous studies found that hyperdivergent subjects had reduced soft tissue thickness in Rhi h -Rhi s , Ss h -Sn s , and U1-LS, compared to hypodivergent subjects [32,33].…”
Section: Discussionsupporting
confidence: 93%
“…Harshal Santosh Patil [7] et al concluded that in skeletal class II, the high-angle group showed greater chin soft tissue thickness at Pog-Pog 'than the low-angle and mean-angle groups; the low-angle group showed greater chin soft tissue thickness at Me-Me' and Gn-Gn 'than the mean-angle and high-angle groups; and that all STC (Soft tissue thickness of the chin) were greater in men than in women. Anthony Tannous Macari [8] concluded that chin soft tissue thickness measurements were smaller in adults in the high-angle group than adults in the mean-angle and low-angle groups; all STC values were higher in males than in females, consistent with the Harshal Santosh Patil's study.…”
Section: The Shape Of the Chin Is Associated With The Vertical Skelet...mentioning
confidence: 99%
“…Soft tissue thickness does not entirely depend on underlying hard tissues; it also depends on age, gender, growth pattern, and underlying malocclusion. Hence, soft tissue assessment is integral to orthodontic treatment planning [7][8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%